THE COPPER AND REDUCED SALINITY EFFECTS ON METABOLISM OF HERMATYPIC CORAL Fungia sp - Moh. Muhaemin (JOURNAL OF COASTAL DEVELOPMENT, 2007)
The research determined the physiological responses in Fungia sp that’s exposed to combination of copper presence and reduced salinit for 12 h. The changes of primary production rate per chlorophyll-a and respiration per surface area were used to determine the stress occur. The results showed that no significant on the respiration rate in any of treatments between treatments or compared with control. Corals exposed to 10 µg.l-1 copper to reduced salinity were unaffected and did not affect the production rate. Coppers exposed to 30 µg.l-1 copper, reduced salinity, and combination of two stressors significantly decreased the production rate of Fungia sp.